MTL30 als Surrogatparameter der Behandlungsqualität chirurgischer Erkrankungen: Etablierung anhand der StuDoQ-Register der Deutschen Gesellschaft für Allgemein- und Viszeralchirurgie = MTL30 as surrogate parameter for quality of surgically treated diseases : establishment based on the StuDoQ register of the German Society for General and Visceral Surgery - Wiegering, Armin; Hardt, Julia; Post, Stefan (Der Chirurg, 2017)
From a sociopolitical aspect there is increasing interest in the quality of healthcare. In this context valid, reproducible, comparable and risk-adjustable markers that are easily identified have become crucial for consistent documentation of quality. We recommend MTL30 (mortality, transfer, length of stay) as one of these markers to consistently measure the quality of large visceral surgical interventions. The MTL30 subsumes a number of known markers that may help to predict postoperative complications. The MTL30 is considered to be fulfilled when a patient on the 30th day following surgery, a) has died b) is still in the hospital or c) has been transferred to another acute care hospital. The evaluation of the StuDoQ register of the German Society for General and Visceral Surgery (DGAV) shows that MTL30 occurs significantly more often than any of the individual parameters. The correlation between MTL30 and other patient-specific risk factors, e.g. American Society of Anesthesiologists classification (ASA), age, etc. enables a risk adjustment.
Gesehen am 21.11.2018